Evaluation of the prevalence, and relationship between nutritional status, malnutrition, and quality of life in cancer patients undergoing chemotherapy in Mashhad, Iran in 2023 - Zeyghami, Ali; Keikhay Moghadam, Hanieh; Babaei, Arvin; Bari, Ali-Reza; Hamedi‑Shahraki, Soudabeh; Shahidsales, Soodabeh; Dahri, Monir (World Nutrition Journal, 2025)
Introduction: Cancer patients face high risks of malnutrition, low muscle mass, and sarcopenia due to decreased intake and treatment side effects. This malnutrition can lead to longer hospital stays, higher mortality, lower quality of life, and poor treatment tolerance. The purpose of this study is to evaluate the prevalence and relationship between nutritional status, malnutrition and quality of life in cancer patients undergoing chemotherapy in Mashhad, Iran in 2023. Method: In a cross-sectional study, we evaluated 237 cancer patients from Razavi, Nazeran, Qhaem, and Omid Hospitals using the Patient-Generated Subjective Global Assessment (PG-SGA). Data analysis was conducted with SPSS version 21. Results: Among the 237 patients assessed, 61.6% were identified as female. The PG-SGA scores indicated that the prevalence of malnutrition and the risk of malnutrition were 89.9% (n=213) and 7.2% (n=17), respectively. Our findings revealed significant differences in physical function, role function, and emotional status dimensions between the malnourished group and the normal/at-risk malnutrition group (P < 0.001). In contrast, no significant differences were found in cognitive function and social function. Furthermore, there were significant variations in fatigue, pain, and appetite levels between the malnourished group and the normal/at-risk malnutrition group, as assessed by the QoL questionnaire. Conclusion: It was determined that 89.9% of cancer patients across all treatment modalities were malnourished and required immediate care. Gastrointestinal cancer was found to have the highest malnutrition rates when compared to other cancer types.